2022
DOI: 10.48119/toleho.1135370
|View full text |Cite
|
Sign up to set email alerts
|

Content analysis of tripadvisor reviews on safe tourism certified restaurants during the Covid-19 pandemic

Abstract: Covid-19 outbreak, which emerged in December 2019, deeply affected the economies. During the Covid-19 outbreak, there was a significant decline in restaurant revenues, foreign currency inflows and employment. The outbreak has caused radical changes in lifestyles and consumer behaviors. The universe considered in this study comprised users who ate at Safe Tourism Certified restaurants in Turkey and commented on the Tripadvisor website. In this study, the content analysis method, which is used in qualitative res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Customers' reviews were bases for comparison. Study [24] also found positive comments (80.6%) on TripAdvisor reviews of 98 restaurants in Turkey. Taste was the most mentioned factor in positive comments while price was the most mentioned factor in negative comments.…”
Section: Literature Reviewmentioning
confidence: 82%
See 2 more Smart Citations
“…Customers' reviews were bases for comparison. Study [24] also found positive comments (80.6%) on TripAdvisor reviews of 98 restaurants in Turkey. Taste was the most mentioned factor in positive comments while price was the most mentioned factor in negative comments.…”
Section: Literature Reviewmentioning
confidence: 82%
“…Significantly, the word 'price' was found in most of the related research studies in different places: Turkey [24], Thailand [19], [3], and Malaysia [28]. This finding shows the fact that customers are really concerned about prices.…”
Section: Literature Reviewmentioning
confidence: 92%
See 1 more Smart Citation